2011
DOI: 10.1186/1476-9255-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine resistin predicts anti-inflammatory effect of glucocorticoids in asthma

Abstract: BackgroundAdipokines are protein mediators secreted by adipose tissue. Recently, adipokines have also been involved in the regulation of inflammation and allergic responses, and suggested to affect the risk of asthma especially in obese female patients. We assessed if adipokines predict responsiveness to glucocorticoids and if plasma adipokine levels are associated with lung function or inflammatory activity also in non-obese (body mass index (BMI) ≤ 30 kg/m2) women with newly-diagnosed steroid-naïve asthma.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
0
32
1
2
Order By: Relevance
“…It is known well that obesity has complex influences on allergic inflammation and is likely an important modifier of the pathogenesis of airway disease in asthma (17). Conversely, Dixon suggested that although the individuals with obesity and asthma may have signs of Th2-mediated inflammation, adipokine derangements in obesity are associated with Th1 rather than Th2 bias (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known well that obesity has complex influences on allergic inflammation and is likely an important modifier of the pathogenesis of airway disease in asthma (17). Conversely, Dixon suggested that although the individuals with obesity and asthma may have signs of Th2-mediated inflammation, adipokine derangements in obesity are associated with Th1 rather than Th2 bias (23).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the association between obesity and asthma is complex and multifaceted and is likely explained by many mechanisms. Recently, a distinctive role is suggested for leptin in the prognosis of asthma in patients with obesity and also a link between leptin and asthma is suggested by some studies (3,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Several effects of adipokines on the brain increase vulnerability to the development of pathological processes in the brain. Adipose tissue secretes a multitude of compounds other than those discussed here, including for example, visfatin, resistin, apelin and chemerin (Adeghate, 2008; Guo et al, 2009; Lehr et al, 2012; Leivo-Korpela et al, 2011; MacDougald and Burant, 2007), for which even less is known about interactions with the brain. While epidemiologic studies have already shown a higher risk of dementia and brain-associated events in association with overweight and obesity during mid-life and to some extent late-life, the endocrine aspects of adipose tissue in relation to these outcomes are virtually unexplored, and could be useful for refining the adipose tissue exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Высокий уровень лептина ассоциируется с более тяжёлыми формами БА, даже у аст-матиков нормальной конституции [14]. По данным Alwan и соавт., концентрация лепти-на в крови статистически значимо выше у больных БА на фоне избыточной массы тела или ожирения, чем у людей с БА и нормаль-ной массой тела [10].…”
Section: рисunclassified